Hearts during ischemia with or without HTK-protection analysed by dielectric spectroscopy. (26th February 2018) - Schaefer, Michael; Gross, Wolfgang; Gebhard, Martha-Maria
Abstract: Objective : We investigated canine hearts during ischemia after aortic cross clamping (UI, n = 20) and after HTK-cardioplegia (HTK, n = 24) at 35 °C, 25 °C, 15 °C, and 5 °C with the aim to compare tissue changes caused by the activity of anaerobic metabolism(AAM), cell membrane destruction(CD), and gap junction uncoupling(GJU). Approach : We measured continuously the complex dielectric spectrum(DS), ATP- and lactate content, extracellular pH, and rigor contracture. To identify changes in DS caused by AAM, CD, and GJU we performed additional experiments on the gap junction-free skeletal muscle. We used heart model simulations to calculate the effect of temperature. Main results : AAM affected the DS at 10 MHz and we found a strong correlation between DS and the proton concentration with a maximum of DS at 10 mmol g −1 dry weight in ATP-concentration. The time of GJU was detected by a characteristic increase in DS and CD by a characteristic decrease at 13 kHz. In comparison to UI, GJU, AAM and CD were delayed by HTK and by hypothermia, indicating a minimization of energy consumption and an improved preservation of tissue structure. Significance : The novel findings were that in UI at 5 °C GJU occurred earlier and AAM remained constant, indicating a less effective preservation in UI by deep hypothermia in contrast to HTK.